A PRESENÇA DO POVO WARAO NO ESPAÇO URBANO DE IMPERATRIZ: Trajetórias de sobrevivência e análise das políticas públicas - FERREIRA, Filipe André Von Nordeck Sousa (2024)
The general objective of this dissertation is to understand the migratory insertion of the indigenous people from Venezuela the Warao into Maranhão, and more specifically, into the city of Imperatriz. This research seeks to understand the characteristics of this migration and analyze public policies established to welcome them. The relevance of this topic is related to the arrival of a large number of Venezuelans to Brazil, via the border of Roraima, starting in 2016. If we analyze the process of mobility and its peculiarities, we understand that the long migratory process of the Warao people is part of an Amazonian geographic and sociological context. The Legal Amazon corresponds to a geographic space of nine states, which includes the southwest of Maranhão, whose main urban center is the city of Imperatriz. Therefore, we established a bibliographical research on the geographic, cultural and sociological specificities of the Warao. Based on this reading, the field research was focused on semi-structured interviews with city public servants, such as an administrative technician, a social worker and the coordinator of a migrant shelter in the city. Outside the scope of the city government, a public defender who advocates on behalf of the Warao people and also a representative of the Warao people were interviewed. Throughout the research, weaknesses in the process of access to public policies and basic rights were observed. It can be understood that these weaknesses occur due to ruptures of various forms: historical ruptures resulting from colonization, institutional ruptures between the city government and the Warao people, but also internal ruptures within the group itself in relation to survival strategies.